2018
DOI: 10.1002/ppul.24123
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary interstitial glycogenosis: Diagnostic evaluation and clinical course

Abstract: The P.I.G. phenotype has not been comprehensively described, and poor recognition and misconceptions about P.I.G. persist. P.I.G. is a disease that presents in early infancy, requires significant medical intervention, and frequently is seen in association with alveolar simplification and/or cardiovascular disease. CT findings include ground glass opacities and cysts. Patients should be monitored for pulmonary hypertension. Without life-threatening comorbidities, many patients do well over time, although respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 21 publications
3
65
0
Order By: Relevance
“…Some decreases in air trapping, septal thickening, lower architectural distortion, parenchymal bands, and peripheral triangular images were observed. However, relevant alterations persisted, similar to the cases reported in the literature . It has been hypothesized that the improvement in the ground‐glass pattern suggests that PIG improves over time, while changes consistent with alveolar simplification might persist …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Some decreases in air trapping, septal thickening, lower architectural distortion, parenchymal bands, and peripheral triangular images were observed. However, relevant alterations persisted, similar to the cases reported in the literature . It has been hypothesized that the improvement in the ground‐glass pattern suggests that PIG improves over time, while changes consistent with alveolar simplification might persist …”
Section: Discussionsupporting
confidence: 83%
“…The literature also reported cases in which PIG is associated with other pathologies, particularly those related to major disorders in lung development. These associations sometimes predict an unfavorable clinical course …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary interstitial glycogenosis is an idiopathic form of chILD that, like NEHI, typically presents during infancy with tachypnea and hypoxemia. Liptzin et al reported clinical findings and long‐term follow‐up on 24 patients with biopsy‐proven interstitial glycogenosis from Children's Hospital Colorado. Histology revealed patchy and diffuse disease in equal numbers.…”
Section: Rare Lung Diseasesmentioning
confidence: 99%